GAMMA RAY BURST FOLLOW-UPS WITH BOOTES-4 - Guziy, Sergey; Castro-Tirado, Alberto J.; Jelínek, Martin; Gorosabel, Javier; Kubánek, Petr; Cunniffe, Ronan Cunniffe; Lara-Gil, Oscar; Tello, Juan C.; Jeong, Soomin; Oates, Samantha R.; Xu, Youdong; Pérez-Ramírez, Dolores; et al. (Одеські астрономічні публікації, 2014)
The Burst Observer and Optical Transient Exploring System (BOOTES), is a global robotic observatory network, which started in 1998 with Spanish leadership devoted to study optical emissions from gamma ray bursts (GRBs) that occur in the Universe. We present shot history and current status of BOOTES-4 telescope. Some details of 38 GRBs followed-up with BOOTES-4 are discussed.